The eloquence of the text and the language of Abo Tammam. A reading in Quranic intertexheality - Jrekous, Tayser; Martakosh, Souleen (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study tries to enter to Abo Tammam's poetic text by the intertextuality entrance which is a modern and eloquent entrance, the purpose of the research is lying in indicate to the poetic of the text by the eloquence of linguistic performance, the study contains the subject gradually, so that writing started to establish the origin of the intertextuality concept as a western and newcomer term. Then it moved to clarify the religious intertextuality as an impact of Quran including its enunciation, meanings and images, then the impact of characters, biography, the study updated address the praise poem through analytical inquiry. It focuses on a great number of poetic intertextuality of Abo Tammam, Maby the reader have not to miss two things first. Abo Tammam's saturation of his Arab Islamic culture, especially the Quranic Second, it points to the poet Abo Tammam's professional through the movements intertextuality which generates the poetic of the done language.